ON GENERALIZED EIGHTH ORDER MOCK THETA FUNCTIONS - Pramod Kumar Rawat (Ural Mathematical Journal, 2020)
In this paper we have  generalized eighth order mock theta functions, recently introduced by Gordon and MacIntosh involving four independent variables. The idea of generalizing was to have four extra parameters, which on specializing give known functions and thus these results hold for those known functions. We have represented these generalized functions as \(q\)-integral. Thus on specializing we have the classical mock theta functions represented as \(q\)-integral. The same is true for the multibasic expansion given.